وﺣدة اﻷﻣﺔ اﻹﺳﻼﻣﯾﺔ ﻓﻲ اﻟﻘرآن اﻟﻛرﯾم )دراﺳﺔ ﻣوﺿوﻋﯾﺔ( (Journal of the College of Education for Women, 2019)
The theme of unity of the topics that figured prominently Quran, cited preachers and scholars verses function on the unity and sense, to lift the nation from Hdtha, saved from the crisis, in an attempt to reunite and heal the rift, and re nation to unity and strength, and conduct on the path religion True, The Quran the unit is the Constitution of the Islamic nation and a safety valve, a strong rope of God. The following us in our research and Rod talk about it lonely in the Quran, and the statement of some form, and means its findings, including: (obey Allah and His Messenger, and referring to the Quran and Sunnah, and talk by saying better, reform between the brothers, call wisdom and good advice, etc.. ..), as Pena main obstacles and barriers that stand in front of the unification Islamic nation, including: (difference idiosyncratic, differences Streptococcus, vanity, self ignorance and lack of knowledge, conspiracies enemies people of Islam), what we only need to strive to overcome and mitigate these barriers so that we can achieve unity of the Islamic nation, and the last prayer is that all praise beto Allah.